2018
DOI: 10.3389/fpls.2018.00478
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Artemisia annua Plant Biomass Artemisinin Content and Guaiacol Peroxidase Activity Using the Arbuscular Mycorrhizal Fungus Rhizophagus irregularis

Abstract: The main objective of this study was to investigate Artemisia annua plant property variations in terms of plant biomass, glandular trichome numbers, artemisinin production and Guaiacol peroxidase (GPOX) activity when plants are in mutualism with AMF. According to the results, A. annua mutualism with AMF significantly increased the most important and pharmaceutically relevant factors of fresh and dry plant biomass. This increase, especially in the biomass of plant herba (leaves), was 30% higher during the veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 37 publications
2
29
3
Order By: Relevance
“…Mycorrhizal plants are more adaptable under adverse conditions such as drought and saline.The activity of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) in the body is signicantly improved, which can slow down the oxidative damage of plants and enhance drought resistance. 37,38 The results of this study showed that the inoculated AMF mainly increased the enzyme activities (SOD, POD, CAT) to eliminate the accumulation of reactive oxygen species caused by drought stress, thereby reducing the damage caused by cell membrane lipid peroxidation. Studies have shown that inoculation can increase the CAT activity of Caragana korshinskii Kom.…”
Section: Discussionmentioning
confidence: 80%
“…Mycorrhizal plants are more adaptable under adverse conditions such as drought and saline.The activity of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) in the body is signicantly improved, which can slow down the oxidative damage of plants and enhance drought resistance. 37,38 The results of this study showed that the inoculated AMF mainly increased the enzyme activities (SOD, POD, CAT) to eliminate the accumulation of reactive oxygen species caused by drought stress, thereby reducing the damage caused by cell membrane lipid peroxidation. Studies have shown that inoculation can increase the CAT activity of Caragana korshinskii Kom.…”
Section: Discussionmentioning
confidence: 80%
“…The plants (Artemisia annua Anamed A-3, Winnenden, Germany) were cultivated in 2017 in Corunca (Mureș County, 46°31'18.18''N and 24°35'53.78''E) as previously described in Domokos et al (2018)…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that vesiculararbuscular mycorrhizae stimulate plant growth in case of Artemisia annua (Chaudhary et al, 2007;Kapoor et al, 2007;Awasthi et al, 2011;Huang et al, 2011;Tan et al, 2013;Fortin and Melchert, 2015;Giri, 2017;Domokos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As a secondary metabolite used mainly in defence mechanisms, production of artemisinin would naturally be induced and enhanced under environmental stresses. Under such adverse conditions the elevation of secondary oxidative stress, which is a consequence of primary biotic/abiotic stress, is in a direct synergistic relationship with artemisinin production [2427]. On such basis, the biotechnological method elicitation which mimics the natural induction of plant stress is the method of choice to enhance the production of artemisinin.…”
Section: Introductionmentioning
confidence: 99%